EFFICACY OF ESOPHAGEAL VARICES ENDOSCOPIC LIGATION - S. A. Gabriel; V. M. Durleshter; A. Y. Guchetl; V. Y. Dynko; D. S. Murashko; V. S. Krushelnitsky (Кубанский научный медицинский вестник, 2016)
The article describes the experience of endoscopic ligation of esophageal varices in 338 patients with liver cirrhosis with portal hypertension from 2009 to 2016. In this paper we analyzed the stages of endoscopic ligation, ligated number of nodes in each patient, the effectiveness of ligation causes of failures.